Blogging in Extensive Reading: Students’ Voice in Blended Learning Classroom - Asri Siti Fatimah; Dian Kardijan; Fera Sulastri (Vision: Journal for Language and Foreign Language Learning, 2020)
The use of a blog as a platform for extensive reading becomes valuable since it provides the possibility of readership and opportunity for interaction and collaboration. As the online journal facilitating users to display information in chronological order and connected to the Internet, the blog also can help students to get a wide variety of reading materials, which should be conducted in extensive reading activities. However, the use of a blog in this study is integrated with the process of learning in the classroom so that the students can use it for reporting their reading activities and share what they read beyond the classroom. This study is conducted during one semester in one of the universities in Indonesia using six students of the first grade joining an extensive reading course as the participants. In this research, a case study is used as a research method. It aims at analyzing the students' perception of the use of blogs in extensive reading. Findings show that the blog is beneficial for promoting the students' reading interest, building autonomy and creativity, and providing a reflective platform. The blog consists of several features allowing students to get the numerous reading sources that are appropriate with their language level and interest. Therefore, it becomes useful since it can facilitate students to build their responsibility to select their reading material and to reflect the progress of their learning activities.